1992
DOI: 10.1055/s-0038-1646284
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Factor VII, Fibrinogen and Plasminogen Activator Inhibitor-1 Activity after Surgical Treatment of Morbid Obesity

Abstract: SummaryThe aim of this study was to determine the effects of the surgical treatment of morbid obesity on some aspects of haemostatic and fibrinolytic function. Measurement of haemostatic and fibrinolytic factors was performed before and again 6 and 12 months after operation in 19 patients suffering from morbid obesity. Surgical treatment resulted in a mean decrease in body weight of 50 kg at 6 months and 64 kg at 12 months. Weight loss was accompanied at 12 months by significant reductions in median (interquar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 20 publications
4
58
1
Order By: Relevance
“…The level of obesity may therefore explain the missing acute reduction in IL-6, fibrinogen and partly hs-CRP, as the present participants were not morbidly obese and had no evidence of metabolic or systemic diseases. However, other studies with similar subject groups have observed significant acute reductions in hs-CRP, 15,[17][18][19][38][39][40] 15,17,39,[41][42][43] and fibrinogen 23,30,[44][45][46] at smaller and similar weight losses (4-20 kg). One explanation could be that the present study was underpowered to detect a significant change in the pro-inflammatory markers after weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The level of obesity may therefore explain the missing acute reduction in IL-6, fibrinogen and partly hs-CRP, as the present participants were not morbidly obese and had no evidence of metabolic or systemic diseases. However, other studies with similar subject groups have observed significant acute reductions in hs-CRP, 15,[17][18][19][38][39][40] 15,17,39,[41][42][43] and fibrinogen 23,30,[44][45][46] at smaller and similar weight losses (4-20 kg). One explanation could be that the present study was underpowered to detect a significant change in the pro-inflammatory markers after weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, the relationship between PAI-1 levels and fat mass was emphasized because it persists after controlling for the other biological variables of the insulin resistance syndrome (10). Weight loss secondary to calorie restriction or surgery is associated with reduced PAI-1 activity (the changes are related to weight loss rather than reductions in the biological insulin resistance level) (11). Interestingly, waist-to-hip ratio, a reflection of central fat accumulation, has been found in women to be the only independent predictor of circulating PAI-1 activity (12).…”
mentioning
confidence: 99%
“…Recent studies have shown that weight loss induced by surgery results in an impressive reduction of insulin resistance (11,21), reduces relevant markers (C-reactive protein, interleukin-6, interleukin-18, and sCD40L) of chronic vascular inflammation (11,(21)(22)(23), and decreases well-established cardiac risk factors that have been shown to be important predictors of cardiovascular morbidity and mortality (26 -30). In addition, surgery improves endothelial dysfunction (24) and reduces key factors responsible for the increased atherothrombotic risk of the morbidly obese patients, such as tissue factor, factor VII, and plasminogen activator inhibitor (PAI)-1 (19,20).…”
mentioning
confidence: 99%